Improving third-year medical students' competency in clinical moral reasoning: Two interventions. Issue 3 (2nd July 2016) - Cummins, Paul J.; Mendis, Katherine J.; Fallar, Robert; Favia, Amanda; Frank, Lily; Plunkett, Carolyn; Gligorov, Nada; Rhodes, Rosamond
ABSTRACT: Background: This article reports on the impact of two ethics interventions implemented for third-year medical students. Previous research validated our institution's model for assessing medical students' competency in medical ethics. Confident in our assessment model, the bioethics faculty sought to improve student performance.Methods : We designed and implemented two additions to the third-year medical ethics curriculum: a written ethics project with faculty feedback, and a standardized glossary of the bioethical concepts addressed by our curriculum. To measure the impact of the written ethics project, we compared students' scores on their comprehensive ethics assessment in 2011, prior to the curricular additions, to the 2013 scores of students who only received the written ethics assignment supplement. To measure the impact of the glossary we distributed it to half of the students sitting for the ethics assessment in 2013, and compared their scores with their classmates' who had not received the glossary.Results: The 2013 students who only received the written ethics project scored 12.5% higher than the 2011 students, and they displayed significant improvement in justifying a resolution of a clinical ethical dilemma. The 2013 students who received the glossary were significantly better at recognizing which principles and concepts of biomedical ethics were relevant to a clinical case and explaining how they created a conflict.Conclusions: Medical student competency in clinical moral reasoning is enhanced by written ethics projects, a faculty feedback component, and access to a glossary of ethical terms.